2020
DOI: 10.9734/cjast/2020/v39i4331143
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Effects of the Climate Change and the Recent Hydromorphological Modification of Vridi Channel (Côte d'Ivoire) on Some Its Hydrochemical Characteristics

Abstract: This work aims to assess the simultaneous effects of the climate change and the hydromorphological modification of Vridi channel on its hydrochemistry. To best estimate, this fact, the seasonal dynamic of the particle size distribution, pH, redox potential, salinity, conductivity, moisture and organic matter contents of Vridi channel sediments have been followed and compared during two different annual periods, where the climate and the hydromorphology of this estuary have been different. The first annual peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As in the case of the physical and chemical parameters assessed by N'Da et al [34], the climate change and the recent development of Vridi channel led to a general decrease in the carbonates and ETM contents, as well as the different P fractions considered in this study. So, the present hydromorphological configuration of this artificial estuary, with the support of the climate change, is similar to a purifier of pollutants from Ebrié system towards Atlantic Ocean in front of Abidajan district.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As in the case of the physical and chemical parameters assessed by N'Da et al [34], the climate change and the recent development of Vridi channel led to a general decrease in the carbonates and ETM contents, as well as the different P fractions considered in this study. So, the present hydromorphological configuration of this artificial estuary, with the support of the climate change, is similar to a purifier of pollutants from Ebrié system towards Atlantic Ocean in front of Abidajan district.…”
Section: Discussionsupporting
confidence: 52%
“…This fact has impacted its hydrochemical functioning. This was illustrated by the recent study of N'Da et al [34], who have shown that the simultaneous impacts of this development with the climate change on the seasonal dynamics of pH, redox potential, conductivity, salinity, particle size distribution, moisture and organic matter contents of its superficial sediments. This would certainly have an effect on the biodiversity of this aquatic ecosystem, in particular on its flora and benthic fauna.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is also the case for their phosphorus contents, which experienced a real drop with this development. On the other hand, this development has very little influence their pH [14,19].…”
Section: Presentation Of the Study Areamentioning
confidence: 99%